Effects of simulated microgravity on the expression profiles of RNA during osteogenic differentiation of human bone marrow mesenchymal stem cells. (5th November 2018) - Li, Liang; Zhang, Cui; Chen, Jian‐ling; Hong, Fan‐fan; Chen, Ping; Wang, Jin‐fu
Abstract: Objectives: Exposure to microgravity induces many adaptive and pathological changes in human bone marrow mesenchymal stem cells (hBMSCs). However, the underlying mechanisms of these changes are poorly understood. We revealed the gene expression patterns of hBMSCs under normal ground (NG) and simulated microgravity (SMG), which showed an interpretation for these changes by gene regulation and signal pathways analysis. Materials and methods: In this study, hBMSCs were osteogenically induced for 0, 2, 7 and 14 days under normal ground gravity and simulated microgravity, followed by analysis of the differences in transcriptome expression during osteogenic differentiation by RNA sequencing and some experimental verification for these results. Results: The results indicated that 837, 399 and 894 differentially expressed genes (DEGs) were identified in 2, 7 and 14 days samples, respectively, out of which 13 genes were selected for qRT‐PCR analysis to confirm the RNA‐sequencing results. After analysis, we found that proliferation was inhibited in the early stage of induction. In the middle stage, osteogenic differentiation was inhibited, whereas adipogenic differentiation benefited from SMG. Moreover, SMG resulted in the up‐regulation of genes specific for tumorigenesis in the later stage. Conclusion: Our data revealed that SMG inhibits the proliferation and inhibits the differentiation towards osteoblasts but promotes adipogenesis. SMG also selects highly tumorigenic cells for survival under prolonged SMG.